Earth worlds and Indigenous dream-making: A reflection on teaching for beauty, repair, and balance - Sumida Huaman, Elizabeth (Revista Española de Educación Comparada, 2023)
Based on long-term educational relationships with Indigenous communities in Peru, the U.S., and Canada, this article reflects on place-based Indigenous education in and out-of-school. From small community-based schools to tribal tertiary learning spaces, Indigenous educational leaders counter schooling as an instrument of coloniality/modernity by centering their knowledges toward relationships of interdependence for good human and planetary living. Confronting ontic and epistemic threats, Indigenous educators and students energize educational design and practice. I propose these processes as Indigenous dream-making, the daily work of honoring the beauty of Native earth worlds, repairing harms to the earth and her beings, and balancing difficult realities with good living. In this time of increased attention to sustainability in education and climate change action, bold Indigenous educational processes challenge human communities to learn in and across earth worlds and to teach for compassionate interconnection that can supplant the course of destructive relentless development.